P528 Adalimumab for patients with Crohn's disease complicated by intra-abdominal abscess: a multi-centre, prospective, observational cohort study. (25th January 2019) - Pineton de Chambrun, G; Pariente, B; Seksik, P; Altwegg, R; Vuitton, L; Stefasnescu, C; Nancey, S; Aubourg, A; Serrero, M; Peyrin-Biroulet, L; Filippi, J; Viennot, S; et al.
Abstract: Background: Management of intra-abdominal abscess complicating Crohn's disease (CD) is challenging. Surgery with delayed intestinal resection is often recommended in this situation. The aim of this study was to estimate the success rate of adalimumab (ADA) in patients with CD complicated by intra-abdominal abscess, after complete resolution of sepsis and abscess, and to identify predictive factors of success. Methods: We performed a multi-centre, prospective, observational cohort study in patients with CD complicated by intra-abdominal abscess. Patients previously treated with an anti-TNF at the time of abscess occurrence, and patients with post-operative abscesses were not eligible. Patients with complete resolution of sepsis and abscess confirmed by MR enterography (MRE) at baseline were included and received 160 mg of ADA at week 0, 80 mg at Week 2, and then 40 mg every 2 weeks. The primary endpoint was ADA success at W24 defined as no steroids use after the 12th week following inclusion, no intestinal resection, no abscess recurrence and no clinical relapse (CDAI > 220 or HBI > 4 and CRP > 10 mg/l at two consecutive visits). Results: From April 2013 to December 2017, 190 patients from 27 GETAID centres were screened. Seventy-three patients were excluded, and 117 were analysed for the primary endpoint. Median age at inclusion was 28 years (inter-quartile range [IQR]:24–36), 58 (50%) patients were male and 39 (35%) were active smokers. Median disease duration before abscess occurrence was 2.4 (0–58.7) months. Thirty-three (28%) patients had been previously exposed to thiopurines. Small bowel CD was responsible for intra-abdominal abscess in 101 (86%) patients. The median size of abscess was 25 (18–40) mm. MRE at baseline showed a visible fistula tract in 67 (58%) patients. Eleven (9%) patients had a percutaneous drainage of the abscess and 114 (97%) patients received antibiotics for a median duration of 21.5 (IQR: 8–31) days. Median CRP and albumin level at inclusion after abscess resolution were 5 (IQR: 2–9) mg/l and 39 (IQR: 36–43) mg/l, respectively. At W24, 83/117 (71%) patients achieved ADA success. Ten (9%) patients underwent an intestinal resection. At least one serious adverse event was reported in 40 patients, with relapse of intra-abdominal abscess in 10 patients, other infections in 7 patients, and gastrointestinal disorders including CD worsening in 27 patients. No death was reported. Conclusions: In this prospective cohort of CD patients complicated by intra-abdominal abscess, ADA success was observed in 71% of cases at W24. During this period, 9% of cases had an abscess recurrence and 9% needed an intestinal resection. No death was reported. Investigation into the predictive factors of ADA success is ongoing.